2020
DOI: 10.21203/rs.3.rs-52184/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Recurrent and Concurrent Patterns of Regional BOLD Dynamics and Functional Connectivity Dynamics in Cognitive Decline

Abstract: Background: The brain’s dynamic spontaneous neural activity and dynamic functional connectivity (dFC) are both important in supporting cognition, but how these two types of brain dynamics evolve and co-evolve in subjective cognitive decline (SCD) and mild cognitive impairment (MCI) remain unclear. The aim of this study is to investigate recurrent and concurrent patterns of two types of dynamic brain states correlated with cognitive decline. Methods: the present study analyzed resting-state fMRI from 62 SCD, 75… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 29 publications
(34 reference statements)
0
2
0
Order By: Relevance
“…However, extensive evidence suggests that FC, even at rest, should be understood as a dynamic measure. In recent years, dynamic FCs obtained from rs-fMRI time series has proven highly informative regarding the underlying brain connectivity patterns, as it enables slight changes over a short period of time to be explored (18)(19)(20). For example, research based on slidingwindow analysis found that the occurrence frequency of a default mode network (DMN)-dominated dynamic FC state was signi cantly different in SCD patients (20).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, extensive evidence suggests that FC, even at rest, should be understood as a dynamic measure. In recent years, dynamic FCs obtained from rs-fMRI time series has proven highly informative regarding the underlying brain connectivity patterns, as it enables slight changes over a short period of time to be explored (18)(19)(20). For example, research based on slidingwindow analysis found that the occurrence frequency of a default mode network (DMN)-dominated dynamic FC state was signi cantly different in SCD patients (20).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, dynamic FCs obtained from rs-fMRI time series has proven highly informative regarding the underlying brain connectivity patterns, as it enables slight changes over a short period of time to be explored (18)(19)(20). For example, research based on slidingwindow analysis found that the occurrence frequency of a default mode network (DMN)-dominated dynamic FC state was signi cantly different in SCD patients (20). However, there have been few attempts to directly compare static and dynamic FCs or to determine whether dynamic FCs could undergo stable and subtle changes in subjects with SCD.…”
Section: Introductionmentioning
confidence: 99%